Developing intercultural competences and creativity: the foundation for successful intercultural communication - Braslauskas, Justinas (Creativity Studies, 2021)
Although various aspects of intercultural communication have been examined in the works of various authors, there is still a lack of more in-depth research to analyse effective intercultural interaction in the context of combining intercultural competences and creativity competences. A number of works on intercultural communication identify only the barriers to effective communication and provide ways to overcome them; they insufficiently focus on the importance of competence development, in particular the role of creativity in ensuring effective intercultural communication. Meanwhile, the role of creativity as a process of generating new ideas and solving problems in intercultural communication is undeniable. There is no doubt that in order to ensure effective intercultural communication, it is necessary to combine intercultural competences with creativity competences. The object of this study is the development of intercultural competencies and creativity competencies in the context of intercultural interaction. The aim of this article is to examine the development of intercultural competencies and creativity as a basis for successful intercultural communication. Through the works of various scholars, the article describes the aspects of intercultural competences and creativity competence development in the context of intercultural interaction, and emphasises the importance of combining these competencies in order to achieve effective intercultural communication. The following methods are applied in the work: analysis and synthesis of scientific literature.